Cloud Computing and Education- A Technical Review - Ramzan, Shahid; Irfan, Dr.Mohd (IJRDO -Journal of Computer Science Engineering, 2016)
The objective of present paper is reviewed the technical Aspect of Cloud Computing on the Education System. The Class room teaching is a changing and Students are becoming more technology oriented and Therefore in his changing environment, it’s important that we think about the latest technologies to incorporate in the teaching and learning process. One of the latest technologies prevailing now days is Cloud Computing. By sharing IT services in the cloud, educational institution can outsource noncore services and better concentrate on offering students, teachers, faculty, and staff the essential tools to help them succeed. Nutshell Cloud computing has the potential for improving the efficiency, cost and convenience for the universities and educational sectors.